A busca das origens na adoção e seus efeitos - Giorgis, José Carlos Teixeira (2015)
Knowing oneself is as well the essence of being human. This feeling, however, is not satisfied with a introjection that go unveiling the fibers of the organism, dissecting each part to bring together after the pieces and get acquainted with the tamed content. Instead, the human being craves more after fulfilling his inner journey: wants to know his origin, how he arose, where he came from, who his ancestors are, how to be situated in a place and also find his nest, their voices and ways, with the certain from this beginning. Different situation is of the adopted son that sooner or later had known of its purely affective host: in him arouse inquiries, questions and concerns that leads to the irrepressible urge to get answers that reach to them sometimes unduly, through relatives or friends, and in other times by, many times precarious, information from their adoptive parents. The willingness of researching the genetic ancestry is a psychological imperative, or an uncertain adventure, leading to unpredictable results, for it manages with the human feelings. This quest for the biological origins has received the legal support and from the doctrines and foreign jurisprudence, as well as from legislation of other people regarding the duly settled adoption, has migrated to the Brazilian nation especially after the 1988’s Constitution, diploma which, knowingly, swelled and protected the individual guarantees, ensuring for its recognition and protection through veneration for principles and due process.Being supported by the dignity of the human being and recognized as a fundamental guarantee, the right to knowledge of the genetic origins, before handled only by the treatises and referred to in sporadic decisions, has won its legal identity with the recent amendment in the adoption institute provided on the Civil Code, now interpreted, supplementary, by the Children and Adolescents Statute, which provides expressly the right of the adopted consult, without further formal preciosity, the records of the action in which he won a socio-affective family. The dissertation, therefore, takes care, of this right and its implications, seen through different shades, with appeal not only to the ordering and their exegesis, but also on the bridges that formulates with other disciplines or sciences, since the effects of this discovery, in face of irreversibility of adoption remain in preventing hereditary diseases and impediments to marriage, in addition to meeting, as stated above, the recurrent curiosity of the adopted son.